ANALISIS EKONOMI DAN KEBIJAKAN SUMBER DAYA ALAM PROVINSI JAWA BARAT - Ahmad Heryawan; Akhmad Fauzi; Aceng Hidayat (Departemen Ekonomi Sumberdaya dan Lingkungan, Fakultas Ekonomi dan Manajemen, Institut Pertanian Bogor, 2014)
This research analyzed the economic aspect of natural resource in West Java Province, particularly fishery and agriculture. The objectives of the research are: (1) to analyze the diversity of natural-resource-based sectors (particularly fishery and agriculture) in West Java Province during 2001-2012 period, (2) to identify and explain the instability of the natural-resource-based sectors in the long term, and (3) to analyze the connection pattern between the instability of the two sectors and its input and output variables. This research was analyzed using Data Envelopment Analysis (DEA), Coppock Instability Index (CII), and correlation. The result of this research shows that: (1) during the period of 2001 – 2012, agriculture sector showed performance towards better direction, while fishery sector tends to fluctuate. The performance of agriculture output could be improved by 8.75% from the existing condition, while the performance of fishery production could be improved up to 23%, (2) interaction between instability index and the input and output (labor, NTP and NTN) shows that there are policy dynamics on the input and output in fishery and agriculture sector, (2) in agriculture sector, NTP and production has positive correlation to CII. This means that the higher the NTP and production, the more instable the farmer’s prosperity is. This is contrary to fishery sector, where the increase of NTN and production tend to stabilize the community’s prosperity